BPAP induces autism-like behavior by affecting the expression of neurodevelopmental genes in Drosophila melanogaster. - Song, Y.; Zhang, X.; Wang, B.; Luo, X.; Zhang, K.; Zhang, X.; Wu, Q.; Sun, M. (Ecotoxicology and Environmental Safety, 2024)
Bisphenol AP (BPAP), an environmental endocrine disruptor, may cause neurodevelopmental disorders affecting human health. Studies have shown that BPAP impacts hormone synthesis and metabolism, causes social behavior abnormalities, and induces anxiety-like behavioral impairments in mice. However, evidence for the neurobehavioral effects of BPAP is still lacking. Here, we examined the toxic effects of BPAP on neurodevelopment using a Drosophila model. We assessed the role of BPAP exposure in autism-like behavior and explored the underlying mechanisms. Our findings indicated that BPAP exposure reduced pupation and eclosion rates and delayed growth in Drosophila. Furthermore, BPAP exposure caused autism-like behaviors, characterized by increased grooming times and aberrant social interactions, along with abnormalities in locomotor activity, as well as learning and memory ability. Mechanistically, we found that BPAP decreases the number of neuroblasts (NBs) and mature intermediate neural progenitors (INPs) in the 3rd larval brain, impairing axon guidance in the mushroom body of the adult Drosophila brain. Additionally, our transcriptome analysis revealed that BPAP exposure alters the expression of neurodevelopment-related genes (Nplp3, sand, lush, and orco) and affects the estrogen signaling pathway (Hsp70Ab, Hsp70Bc, Hsp70Ba, and Hsp70Bb). These changes potentially explain the BPAP-induced autism-like behavior in Drosophila.